Strategi Pendidikan Islam Dalam Pembentukan Akhlak Siswa Sd Islam Tebuireng Ir. Soedigno - Abd Chamid; Dian Triana; Atim S (Arsy : Jurnal Studi Islam, 2019)
This study aims to determine the benefits of Islamic education strategies in the formation of students' morals at SD Islam Tebuireng Ir. Soedigno. The location of the research is SD Islam Tebuireng Ir. Soedigno. The reasons for choosing the location at SD Islam Tebuireng Ir. Soedigno because this school is a school founded by the KH Foundation. Muhammad Hasyim Asy'ari in Tebuireng Jombang, who occupied the waqf land from Ir. Soedigno, which is located in the village of Kesamben, Jombang district, although this school is located in a village, it has made rapid progress in the field of education compared to the surrounding schools that have been around for a long time. So that researchers are interested in knowing more about the education system in it. The Islamic education strategy applied at SD Islam Tebuireng Ir. Soedigno such as smiles, greetings, and greetings, murotal playback, Islamic songs and national obligatory songs, arranging sandals and shoes, dhuha prayer, dhuha motivation for reading Asmaul Husna and its meanings, Learning the Qur'an, dhuhur prayer is very effective and very supportive once with the learning applied at SD Islam Tebuireng Ir. Soedigno, in the early days the guardians of students at SD Islam Tebuireng Ir. Soedigno many parents complain that their children are naughty, but gradually after going through the process of Islamic education and our application of applying good morals, most students have turned into good children, initially the child was brave with his parents, brave with the teacher, after Gradually through the application of correct Islamic education, both in theory and practice, Alhamdulillah, the student's condition was stable, but those who were originally naughty at home ended up not being naughty.